(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Artificial Intelligence (AI) has increasingly become significant in healthcare, including dentistry, and so understanding the perspectives of future dental professionals is crucial for its effective implementation. Past studies indicate a general awareness of AI among dental students and practitioners; however, gaps in knowledge and practical application remain. This study aimed to assess knowledge, attitudes, and practices regarding AI in dentistry among dental students, interns, and dentists in Saudi Arabia. Methods: A cross-sectional study was conducted from July to November 2024 using a self-structured questionnaire. Participants consisted of dental students, interns, and licensed dentists recruited through social media platforms across Saudi Arabia. Statistical analyses were performed to evaluate relationships between demographic factors and AI knowledge and awareness. Results: A total of 839 participants (mean age: 24.9; 64.5% female) were included. Notably, 90.6% of respondents expressed awareness of AI, yet 46.0% reported having limited to no understanding of its functionality. A significant majority (68.2%) recognized potential AI applications in dentistry, with 85.0% optimistic about its transformative impact. While 78.0% supported the integration of AI into dental education, concerns persisted regarding its potential to replace human expertise, with 44.0% expressing skepticism. Knowledge levels showed that 49.6% demonstrated high knowledge, yet 11.2% had low knowledge of AI applications. Significant associations were found between knowledge and qualification level (p=0.045) as well as awareness and place of work (p<0.0001). Conclusion: This study reveals a high level of awareness of AI among dental professionals in Saudi Arabia, coupled with notable gaps in understanding and practical application. Most participants support the incorporation of AI into dental education, highlighting the need for comprehensive training programs. As AI technology continues to evolve, addressing these gaps will be essential for integrating AI effectively into clinical practices, ensuring readiness for future advancements in dentistry. Our findings underscore the importance of enhancing educational frameworks to better prepare dental professionals for the integration of AI technologies in their practice.